Group Mutual Exclusion - Role Processes - Cenci, Karina M. (2011)
This paper presents an extension to group mutual exclusion (GME) where processes join a group with a role (shared, exclusive) in each stage. The properties that must guarantee a solution to GME are: mutual exclusion, bounded delay, progress and concurrency. For this new situation, a new property role mutual exclusion is introduced. A solution is proposed in a network with no share memory whose members commu- nicate by messages. The proposed algorithm is composed of two players: groups and processes, where groups are passive players and processes are active players. For the coordination access to the resource, each group has been assigned a quorum.